LHRH conjugated gold nanoparticles assisted efficient ovarian cancer targeting evaluated via spectral photon-counting CT imaging: a proof-of-concept research. Issue 9 (6th February 2023) - Kumar, Dhiraj; Moghiseh, Mahdieh; Chitcholtan, Kenny; Mutreja, Isha; Lowe, Chiara; Kaushik, Ajeet; Butler, Anthony; Sykes, Peter; Anderson, Nigel; Raja, Aamir
Abstract : Emerging multifunctional nanoparticulate formulations take advantage of nano-meter scale size and surface chemistry to work as a therapeutic delivery agent and a diagnostic tool for non-invasive real-time monitoring using SPCCT imaging technology. Abstract : Emerging multifunctional nanoparticulate formulations take advantage of nano-meter scale size and surface chemistry to work as a therapeutic delivery agent and a diagnostic tool for non-invasive real-time monitoring using imaging technologies. Here, we evaluate the selective uptake of 18 nm and 80 nm sized gold nanoparticles (AuNPs) by SKOV3 (4 times higher) ovarian cancer (OC) cells (compared to OVCAR5) in vitro, quantified by inductively coupled plasma (ICP) and MARS spectral photon-counting CT imaging (MARS SPCCT). Based on in vitro analysis, pristine AuNPs (18 nm) and surface modified AuNPs (18 nm) were chosen as a contrast agent for MARS SPCCT. The chemical analysis by FTIR spectroscopy confirmed the luteinizing hormone-releasing hormone (LHRH) conjugation to the AuNPs surface. For the first time, LHRH conjugated AuNPs were used for in vitro and selective in vivo OC targeting. The ICP-MS analysis confirmed preferential uptake of LHRH modified AuNPs by organs residing in the abdominal cavity with OC nodules (pancreas: 0.46 ng mg −1, mesentery: 0.89 ng mg −1, ovary: 1.43 ng mg −1, and abdominal wall: 2.12 ng mg −1 ) whereas the MARS SPCCT analysis suggested scattered accumulation of metal around the abdominal cavity. Therefore, the study showed the exciting potential of LHRH conjugated AuNPs to target ovarian cancer and also as a potential contrast agent for novel SPCCT imaging technology.